Better information sharing, or "share or be damned"?. Issue 5 (12th October 2015) - Grace, Jamie
Abstract : Purpose: – The purpose of this paper is to explore the ramifications of developments in surveillance policies and technologies for information sharing cultures in a "public protection routine". Design/methodology/approach: – This conceptual paper uses a mixed theoretical, legal and policy-based approach to inform this exploration of the ramifications of developments in surveillance policies and technologies. Findings: – This conceptual paper concludes that developments in surveillance policies and technologies as part of the "public protection routine" will result in a damaging and hasty culture of "share or be damned" unless a more careful approach to new information sharing approaches is developed. Otherwise, an increasing bureaucratisation of risk management through surveillance will lead to a disregard for the fine balance between public protection, procedural rights and privacy. Originality/value: – The originality and value of this conceptual paper is considerable – as some of the case studies discussed are very recent ones, and ones that represent an acceleration of the problems within the "public protection routine" which this paper seeks to unpick.